2017
DOI: 10.2174/1566523217666170412110724
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-derived Extracellular Vesicles for Renal Repair

Abstract: Transplantation of autologous mesenchymal stem cells (MSCs) has been shown to attenuate renal injury and dysfunction in several animal models, and its efficacy is currently being tested in clinical trials for patients with renal disease. Accumulating evidence indicates that MSCs release extracellular vesicles (EVs) that deliver genes, microRNAs and proteins to recipient cells, acting as mediators of MSC paracrine actions. In this context, it is critical to characterize the MSC-derived EV cargo to elucidate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 99 publications
0
69
0
Order By: Relevance
“…Collectively, these observations suggest that EVs produced by Lean-MSCs might mitigate cellular injury by modulating multiple reparative pathways. Current evidence suggests that MSC possess potent immunomodulatory properties that are primarily mediated by the release of EVs [36], which carry anti-inflammatory elements in the form of genes, proteins, and microRNAs [8,37]. Furthermore, we have recently shown that knocking down the anti-inflammatory gene IL-10 in MSC-derived EVs blunts their capacity to repair the poststenotic kidney, implying that the salutary effects of EVs are mediated by their anti-inflammatory cargo [9].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these observations suggest that EVs produced by Lean-MSCs might mitigate cellular injury by modulating multiple reparative pathways. Current evidence suggests that MSC possess potent immunomodulatory properties that are primarily mediated by the release of EVs [36], which carry anti-inflammatory elements in the form of genes, proteins, and microRNAs [8,37]. Furthermore, we have recently shown that knocking down the anti-inflammatory gene IL-10 in MSC-derived EVs blunts their capacity to repair the poststenotic kidney, implying that the salutary effects of EVs are mediated by their anti-inflammatory cargo [9].…”
Section: Discussionmentioning
confidence: 99%
“…EVs are secreted by MSCs and are present in the original cell. A large amount of evidence has indicated that MSC-derived EVs can alleviate both acute and chronic kidney injury and preserve renal function, which has led to cell-free treatment in renal injury repair [5]. RNAs expressed in EVs are regarded as the most functional elements of renal injury repair, and the main RNAs in huMSC-derived EVs are miRNAs [7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, huMSC-derived EVs also exhibit therapeutic effects in the repair of kidney injury. Furthermore, Nargesi et al have confirmed the therapeutic effects of MSC-derived EVs in a kidney injury model as well as the underlying mechanisms [5]. It has also been shown that RNAs, especially microRNAs (miRNAs), play key roles in kidney injury repair, and the main RNAs in EVs are miRNAs [6-8].…”
Section: Introductionmentioning
confidence: 99%
“…Injected MSCs can inhibit tubular cell apoptosis and interstitial fibrosis while stimulating proliferation of tissuespecific progenitor cells. Although MSCs can engraft in renal tubular and endothelial cells, regenerative actions are primarily mediated by EVs (157,158).…”
Section: Extracellular Vesicles As a Therapeutic Tool In Renal Transpmentioning
confidence: 99%